(untitled) (Jurnal Pendidikan Fisika, 2022)
One of the impacts of the Covid-19 pandemic in the world of education is a change in the learning process from face-to-face learning to online learning. To compensate for these changes, it is necessary to integrate technology in learning. The goal of this study is to design thematic learning at the elementary school level by integrating the Internet of Things (IoT) related to climate change parameters. The method in this study uses research and development of IoT-based measuring instruments using the Lolin V3 MCU node, with sensors for temperature, air pressure, humidity, altitude, and light intensity. The research respondents were 20 students. Data collection was carried out using a questionnaire containing four aspects, namely, usability, ease of use, aspects of learning ease, and satisfaction. The results showed that the reliability value > 0.6 and the level of student acceptance of the product was 3.4 with effective criteria. Based on the findings, this instructional design has potential opportunities to increase student engagement even though it is limited in networking. So it can be concluded that IoT-based learning media can be applied as a thematic learning model at the elementary school level during the Covid-19 pandemic.